A Framework of an Interior Design Work Delivery Process - Mustapha, Arniatul Aiza; Mohamad, Mohamad Fadhil; Ahmad Noorhani, Nur Maizura (International Journal of Sustainable Construction Engineering and Technology, 2021)
Despite their minor position within the architectural industry, interior designers play a significant role in the national economy. In compliance with the Architect Rule, the present Interior Design Institution (MIID) in Malaysia is governed by the LAM. The interior designers are keen to comply effectively with this new legislation in the interior design. The interior design process is somewhat close to the architecture process, which typically consists of three key phases of the entire design. The interior design professionals carry out interior design work in accordance with the case and practice the principles in their own way and in their own structures. This leads to the variety of stages, processes and work structures that pose problems, consequences and impacts for stakeholders, in particular the client and the interior designer themselves. This helps the workflow and the interior project delivery process to be streamlined. The objectives are to determine the flow, process, scope and elements of the indoor project delivery practice, to make the scope and elements of the indoor project delivery work process compatible with the other work practice plan, as well as to make a proposal on the indoor design work development plan. The qualitative approach to the research involves the use of systematic literature review, content analysis on interior design, project process practice from approved documentation and related documents, and a series of interviews with members of the interior project team and stakeholders, triangulation and confirmation. This analysis will provide useful information to the client, interior designers themselves and those involved in the project. The IDWDP framework may eliminate job interruptions, task management, clashing of works, and coordination of work.